Effectiveness of Planned Teaching Programme on Knowledge Regarding Management of Common Behavioral Problems of School Children among Primary School Teachers - Sreejamol.M.G; Anju Jose; Saranya Unnikrishnan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Infancy and childhood are of supreme importance in determining the future behavior. Behavioral problemsalways require individual attention. Teachers spend most of the school hours with children so that they candetect the signs and symptoms of these problems at the earliest.The Title of the Study: Effectiveness of planned teaching programme on knowledge regarding managementof common behavioral problems of school children among primary school teachers in selected school inErnakulumObjectives;1.Assess the knowledge of primary school teachers regarding the management of commonbehavioral problems of school children.2. Evaluate the effectiveness of planned teaching program onknowledge of primary school teachers regarding the management of behavioral problems of schoolchildren.3.Associate the socio demographic variables with the pretest & post test knowledge scoresMethodology: The research approach used in the present study was quantitative and research design wasone group pre test post test design. The study was conducted among 30 teachers with the eligibility criteriafollowing purposive sampling technique. The tools used for the study were structured questionnaire.Results : The mean post- test knowledge score (16.18) is significantly (p = 0.001) higher than the mean pretest score(13.7).This shows that structured teaching programme was effective in improving the knowledgeof teachers regarding behavioral problems. There is no association between pretest & post test knowledgescores with demographic variables.Conclusion: The study finding point out the responsibilities of a health professional to enlighten and educatethe teachers regarding management of behavioral problems of school children